Mechanical Behaviors of Hybrid Composites Reinforced with Epoxy Resin - Harikrishna V.; Kumar K. V. (Журнал інженерних наук)
Natural fibres have emerged as a renewable and cheaper substitute to synthetic materials such as glass and carbon. A composite material can be defined as combining two or more materials that result in better properties. The constituents are reinforcement, and the other is a matrix. The main advantages of composites are high strength, stiffness combined with low density. As natural fibres are gaining more importance in recent times, many industries are focusing on these natural fibre composites, so that is why they are used as a component in composite materials. In this experiment, the analysis aims to characterize different natural fibres when combined with different ratios of the coconut coir and the bamboo. So, to fabricate the specimen, the hand lay-up method is used. The coconut coir and the bamboo composition are considered in three different variations. Then the natural fibres are subjected to resin and hardener compositions to test the suitability, tensile strength, flexural strength, and shore hardness test. We also conduct static analysis through ANSYS software.